Alterations of resting-state functional network centrality in patients with asthma: evidence from a voxel-wise degree centrality analysis. Issue 14 (26th September 2018) - Li, Qiu-Gen; Zhou, Fu-Qing; Huang, Xin; Zhou, Xiong; Liu, Chao; Zhang, Ting; Li, Huan-Yu; Wu, Xiao-Rong; Wang, Jun
Abstract : Several previous studies have reported that asthma patients have abnormal brain activities, whereas alterations in the resting-state network still remain unknown. The aim of this study was to investigate the changes in functional network centrality in asthma patients using voxel-wise degree centrality (DC) method. Asthma patients and healthy controls (HCs) were matched closely in age, sex, and education of participants. The DC method was used to evaluate the functional network centrality. The receiver operating characteristic curve was used to distinguish the asthma group from the HCs group. The Pearson correlation coefficient was used to explore the relationship between the observed mean values of DC in different brain areas and the behavioral performance. Compared with HCs, DC values were significantly decreased in the right middle temporal gyrus and the right putamen of asthma patients. In contrast, in asthma patients, DC values were markedly increased in the right posterior lobe of the cerebellum, right inferior temporal gyrus, left superior frontal gyrus, left postcentral gyrus and inferior parietal lobule, left middle frontal gyrus, and left postcentral gyrus. However, there was no relationship between the observed mean DC values in different brain areas and the behavioral performance. The results showed that the DC values were altered in various brain regions of asthma patients, which were related to default mode network, the cortex–basal ganglia network, the frontoparietal network, and the sensorimotor network, leading to some useful information for clinical studies in asthma patients.